Design and Modelling of Ballscrew Linear Guide Actuator for Earthquake Shaking Table (EST) Based on Neural Network - Halimatus Sa’diyah; Purwadi Agus Darwito; Tavio Tavio; Murry Raditya (IPTEK Journal of Proceedings Series, 2020)
Earthquake Shaking Table (EST) is a device which can simulate an earthquake motion. This device is used to test the strength of a building structure against an earthquake motions before it’s actually made. EST uses a variety of actuators one of them is ball-screw linear guide actuator. The EST used in this project is a bi-axial type which uses 2 linear actuators to simulate the x-axis and y-axis movement of earthquake, each of them used bipolar stepper motor as the main rotary-actuating device. This project models the linear guide actuator using backpropagation neural-network algorithm. The model is built with empirical method using datas taken from the real behavior of both linear actuators. The datas include acceleration, displacement, and velocity of both actuators and they are used to train the neural network using backpropagation with Levenberg-Marquadt method. Simulation is done using Simulink and the results show that model is able to produces nearly same exact movement with the real hardware with error approximately 0,214 % and 0,685% respectively for both actuators.